FACTORS ASSOCIATED WITH STUNTING INCIDENCE IN TODDLERS IN NORTH KALIMANTAN - Nurul Hidayatun Jalilah; Ririn Ariyanti; Selvia Febrianti (Jambura Journal of Health Sciences and Research, 2022)
Stunting is a condition where the height index for age is below minus 2 standard deviations based on WHO standards. Stunting is caused by the impact of nutritional deficiencies during the first thousand days of life. The purpose of this study was to determine the factors associated with the incidence of stunting in children aged 9-59 months. The type of this research is quantitative, observational analytic study with cross-sectional design. A total of 120 samples were selected by simple random sampling. This research was conducted from August to September 2021. Data was collected by measuring height, interviews and filling out questionnaires. Statistical analysis using Chi-square test and multiple logistic regression. The results showed that the proportion of stunting was 44,2% and normal was 55,8%. The results of the statistical test showed that there was a significant relationship between early complementary feeding, water sources, and place of residence with the incidence of stunting. This study suggests that the government, health agencies, communities and related parties collaborate to implement government policies to reduce the risk of stunting. For health education, it is recommended to be involved in providing health education in the form of counseling that can prevent stunting.